Efeito da meditação natural stress relief na ansiedade de estudantes universitários com transtorno de ansiedade social : ensaio clínico randomizado e controlado - Souza, Thiago Henrique Almeida (2017)
Mental disorders have an important socio-economic impact on the world. Among the different types of mental disorders, anxiety ones are among the most prevalent, being that social anxiety disorder (SAD) stands out as one of the most limiting anxiety disorders for individuals and is associated with poor academic performance, which directly impacts university students. In addition, your treatment is still a challenge. Alternative treatments considered effective, such as meditation, are often inaccessible to lots of people, especially for students. An interesting alternative came in the attempt to resolve this issue, the Natural Stress Relief (NSR) meditation, via a simple and self-administered program, in a more accessible way. Therefore, the aims of this study were to evaluate the effect of NSR meditation on anxiety of university students with SAD. For that, we selected university students of both sexes, diagnosed with SAD by SPIN. The volunteers were allocated to one of two groups: NSR (n = 18) or Waiting list (n = 18). NSR group individuals performed two sessions per day of NSR meditation (15 min per session) during four weeks, in which first and last sessions were performed in the Laboratório de Fisiologia do Comportamento. Individuals belonging waiting list group did not practice any technique. All volunteers had their general symptoms of anxiety and social anxiety symptoms assessed by the hospital scale of anxiety and depression (HADS-A) and SPIN, respectively. Levels of state anxiety were also evaluated by the numerical tension scale (NTS), the state-trait anxiety inventory (STAI), and physiological indicators records (electromyographic gastrocnemius muscle activity, heart rate, temperature of extremity and skin conductance); and trait anxiety levels were assessed by the trait subscale of the STAI. In addition, One day after last session, volunteers were individually submitted to a social anxiety induction test. Data were analyzed by means of appropriate statistical tests. The results showed that the practice of NSR meditation reduced trait anxiety levels after four weeks (STAI-T); reduced weekly general anxiety symptoms (HADS-A) and social anxiety symptoms (SPIN); and reduced subjective levels of state anxiety (STAI-S and NTS) after the first and last session, but no changes were observed in the physiological indicators of anxiety. In addition, data analysis revealed that four weeks of meditative practice were not sufficient to prevent changes in levels of state anxiety (STAI-S, NTS and physiological indicators) elicited by a social anxiety induction test. At the end of the fourth week, most of NSR group volunteers were classified as presenting normal anxiety symptoms and were no longer categorized as presenting with SAD. Finally, this study showed the anxiolytic effect of NSR meditation in university students diagnosed with SAD according to SPIN.